High speed titanium coating by Supersonic Laser Deposition - LUPOI, ROCCO (My University, 2011)
The importance of metal coating technologies drives the continuous improvement of metal deposition techniques for application in a wide range of industrial sectors. This work presents the foundations of a new process technology f or the deposition of t itanium coatings on steel tube substrates using supersonic powder streams and impact site laser heating , known as Supersonic Laser Deposition (SLD). M etallic deposits are obtained under appropriate impact conditions without the need for exceeding the melting point of the deposited material or substrate leading to improved coating quality. Details of the exp erimental approach are presented along with the general characte ristics of the titanium coating produced using this novel coatings method.
PUBLISHED
Keywords: Laser deposition; CFD; Tubes; Titanium coatings; Cold Spray; SLD